Money Laundering Risks Posed By Mobile Money Services - Thai Ha Van (Technium Social Sciences Journal, 2021)
Mobile money service has been proved an effective tool in financial industry in recent years around the world. Although this kind of financial service brings a number of advantages, many concerns have been raised regarding potential issues that may stem from the use of mobile money. Among these concerns are the issues of using mobile money to facilitate money laundering activities and terrorist financing. In order to mitigate those potential risks for financial system in general, this paper seeks to explore the mobile money characteristics that may pose risks to anti-money laundering and terrorist financing system. This work is based on the available information from scientific research, articles and reports, and other sources.